The Use of â€œFermeherbafitâ€ (Mixed Herbs) in Broiler Chicken Feed on Performance and Cholesterol profile - Hartoyo, Bambang; Iriyanti, Ning; Rimbawanto, Efka Aris (ANIMAL PRODUCTION, 2018)
This research was aimed to imporve of broiler chiken performance and reduce the blood, meat and liver cholesterol levels. Â This research used 100 female broilers MB 200 Platinum DOC which were reared for 5 weeks at battery-postal cages. The treatments were R0= control/ 0% fermeherbafit; R1= used 2% fermeherbafit; Â R2= used 4% fermeherbafit; R3= used 6% fermeherbafit. The experimental designÂ was carried out using a complete randomized design. Data were analyzed by analysis of variance (ANOVA). The results showed that the use fermeherbafit did not showed any significant differences (P>0.05) in feed consumption, absolute growth, relative growth and carcas percentage. However, it showed Â significant differences (P<0.05) in blood and breast meat cholesterols. The average for Performance (feed consumption by 3268.775Â±293.421 g/bird; absolute growth by 1684.92Â±126.12; relative growth by 0.3682Â±0.0019; carcas percentage by 74.61Â± 1.12%). Â Blood cholesterol Â 89.20+12.76 mg/dlÂ (R3) up to 111.80+17.02 mg/dl (R0); Breast meat cholesterol 150.03+11.64 mg/g (R3) up to 174.88+8.53 mg/g (R0); Leg meat cholesterol 173.00+7.21 (R1) up to 152.15+17.83 mg/g (R3); Liver cholesterol 83.37+31.01 Â mg/g (R0) up to 102.75+1.68 mg/g (R3). Conclusion of this research was that the Fermeherbafit could be used in broiler feed up to 6% which could reduce blood and breast meat cholesterols. Â